Gut microbiota-dependent catabolites of tryptophan play a predominant role in the protective effects of turmeric polysaccharides against DSS-induced ulcerative colitis. Issue 20 (25th August 2021) - Yang, Chengcheng; Du, Yao; Ren, Daoyuan; Yang, Xingbin; Zhao, Yan
Abstract : Turmeric polysaccharide supplementation effectively ameliorated DSS-induced ulcerative colitis by modulating the gut microbiota and improving microbial metabolites and gut barrier function. Abstract : Gut barrier dysfunction is triggered by gut microbiota dysbiosis that is closely associated with ulcerative colitis. Recently, more attention has been devoted to the ability of the non-digestively colon-targeted plant polysaccharides to regulate the function and composition of the intestinal microbiota. Here, we first studied the prophylactic capacity of turmeric polysaccharides (TPS) to ameliorate dextran sulfate sodium (DSS)-induced gut microbiota imbalance. The results revealed that TPS administration could greatly improve the pathological phenotype, gut barrier disruption and colon inflammation in colitis mice. Besides, targeted metabolomics or 16S rRNA-based microbiota analysis demonstrated that TPS alleviated gut microbiota dysbiosis caused by DSS, especially increasing the abundance of probiotics associated with tryptophan metabolism, such as Lactobacillus and Clostridia-UCG-014, where the cecal tryptophan catabolite indole-3-acetic acid (IAA) and its ligand aryl hydrocarbon receptor (AhR) expressions were sharply increased by TPS treatment in colitis mice. Expectedly, TPS was found to exert its gut barrier functions through the activation of AhR to upregulate epithelial tight junction proteins. These findings highlight the protective effects of TPS against ulcerative colitis by modulating the gut microbiota and improving microbial metabolites and gut barrier function.